Sistema para la administración del Laboratorio de Informática : SILABINFO (2015)
In this document a synthesis will be made related to the design, development and start-up of the integrated system for the administration of the SILABINFO computer lab that contains: General Objective of the project, specific objectives, Achievements and products, problems faced and solutions, work future and conclusions of the project.